2020
DOI: 10.3389/fcell.2020.00442
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of Transcription Factors in Gastric and Colorectal Cancer Stem Cells Identification and Eradication

Abstract: Gastric and colorectal cancers have a high incidence and mortality worldwide. The presence of cancer stem cells (CSCs) within the tumor mass has been indicated as the main reason for tumor relapse, metastasis and therapy resistance, leading to poor overall survival. Thus, the elimination of CSCs became a crucial goal for cancer treatment. The identification of these cells has been performed by using cellsurface markers, a reliable approach, however it lacks specificity and usually differs among tumor type and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 274 publications
(329 reference statements)
1
24
0
Order By: Relevance
“…Although CICs and somatic stem cells exhibit similar transcription factors (TFs), including SOX2, OCT4, NANOG, KLF4, and c-Myc, several studies have demonstrated that the abnormal expression of some distinctive TFs [ 64 ] have a crucial role in the reprogramming of these cells [ 65 ]. In this case, overexpression of TFs results in dysregulation of associated signaling pathways that are linked with CIC lineage and differentiation phenotype [ 66 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although CICs and somatic stem cells exhibit similar transcription factors (TFs), including SOX2, OCT4, NANOG, KLF4, and c-Myc, several studies have demonstrated that the abnormal expression of some distinctive TFs [ 64 ] have a crucial role in the reprogramming of these cells [ 65 ]. In this case, overexpression of TFs results in dysregulation of associated signaling pathways that are linked with CIC lineage and differentiation phenotype [ 66 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, overexpression of TFs results in dysregulation of associated signaling pathways that are linked with CIC lineage and differentiation phenotype [ 66 ]. Transcriptional regulation occurs when certain TFs bind to the DNA at binding sites of a promoter and affect the transcription of the regulated gene via interactions with their gene promoters [ 65 , 66 ]. In this circumstance, TFs may have a crucial role in the maintenance of CIC stemness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to this continuous proliferation and differentiation of cells, dysregulation in the proliferation and/or differentiation pathways within these cells can result in forming CRC CSCs [ 33 ]. Although the origin of CRC CSCs is still debated today, ultimately, among several other pathways, dysregulations within the Wnt [ 36 ], Notch, and TGF-β signaling pathways of the intestinal epithelial cells have all been found to contribute to the stemness of CRC CSCs [ 2 , 33 , 35 , 37 ]. As a result of these efforts, various genes associated with these pathways have been identified as potential biomarkers for CRC CSCs [ 2 , 34 , 38 ].…”
Section: The Role Of Mirnas In Colorectal Cancer Stem Cellsmentioning
confidence: 99%
“…As a result of these efforts, various genes associated with these pathways have been identified as potential biomarkers for CRC CSCs [ 2 , 34 , 38 ]. In addition to biomarkers directly associated with these pathways, general markers found in several different types of stem cells and CSCs, such as NANOG, OCT-3/4 (also known as POU5F1), and SOX2, are highly expressed in CRC CSCs [ 2 , 33 , 34 , 37 , 38 ]. In addition to these general markers for stemness, it has been well-documented that CD24, CD44, CD133, LGR5, ALDH1, CXCR4, DCLK1, and EpCAM (also known as ESA) can also be used to identify CRC CSCs [ 2 , 19 , 20 , 33 , 34 , 38 , 39 , 40 , 41 ].…”
Section: The Role Of Mirnas In Colorectal Cancer Stem Cellsmentioning
confidence: 99%